Personal Branding of Female Virtual Biography Users on the Bumble Dating Application in a Romantic Relationship - Lestari, Anggita; Salma, Siti; Hanaf, Hanafi; Reza, Faisal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Bumble is a dating platform that empowers women during the initiation phase of romantic relationships. With the